Canary girls : a novel - Chiaverini, Jennifer (William Morrow, an imprint of HarperCollinsPublishers, 2023)
Early in the Great War, men left Britain's factories in droves to enlist. Struggling to keep up production, arsenals hired women to build the weapons the military urgently needed. "Be the Girl Behind the Man Behind the Gun," the recruitment posters beckoned. Thousands of women--cooks, maids, shopgirls, and housewives-answered their nation's call. These "munitionettes" worked grueling shifts often seven days a week, handling TNT and other explosives with little protective gear. Among them is nineteen-year-old former housemaid April Tipton. Impressed by her friend Marjorie's descriptions of higher wages, plentiful meals, and comfortable lodgings, she takes a job at Thornshire Arsenal near London, filling shells in the Danger Building-difficult, dangerous, and absolutely essential work. Joining them is Lucy Dempsey, wife of Daniel Dempsey, Olympic gold medalist and star forward of Tottenham Hotspur. With Daniel away serving in the Footballers' Battalion, Lucy resolves to do her bit to hasten the end of the war. When her coworkers learn she is a footballer's wife, they invite her to join the arsenal ladies' football club, the Thornshire Canaries. The Canaries soon acquire an unexpected fan in the boss's wife, Helen Purcell, who is deeply troubled by reports that Danger Building workers suffer from serious, unexplained illnesses. One common symptom, the lurid yellow hue of their skin, earns them the nickname "Canary Girls." Suspecting a connection between the Canary Girls' maladies and the chemicals they handle, Helen joins the arsenal administration as their staunchest, though often unappreciated, advocate. The football pitch is the one place where class distinctions and fears for their men fall away. As the war grinds on and tragedy takes its toll, the Canary Girls persist despite the dangers, proud to serve, determined to outlive the war and rejoice in victory and peace.